(untitled) (Biological Sciences - PJSIR, 1995)
A test was conducted at NARC, Islamabad toevaluate 43 entries of wheat forresistance to oat-bird cherry aphid. Four of the entries, namely, Faisalabad-85, PARI-73, Rawal-87 and Punjab 81 were found to be resistant, 13 were moderately resistantand26werehighlysusceptible.Anexperiment wasalsoconducted totesttheefficacy ofPirimore, Dimlore and Neem oil for control of English grain aphid. Pirimorc wastested atthree rates (250,400 and 500 gmlha), Dimlore attwo rates (400 and500 ml/ha) andNeem oil attworates (5and 10ha). InthePirimore and Dimlore treated plots, 98% aphid mortality was observed after 24 hr, whereas in the plots treated with Neem oil it was 66 to 78%, compared to 35% natural mortality in the check. Three days after treatment, aphid mortality was 100% in the plots treated with Pirimore and Dimlore, 84% in plots treated with Neem oil and 47% in the check plots. The mortality percentage after one week declined to 79-90% probably due to rapid degradation of insecticides.